Structural Health Monitoring by Identification Dynamic Properties and Load Rating Factor at Multi-span Prestressed Concrete Girder Bridge - Kusumawardani*, Rini; Kusbiantoro, Arief; Nugroho, Untoro; Novita, Erlia Dewi; Nugroho, Imam Agus; Azizah, Kirana Prasetya; Upomo, Togani Cahyadi (Graduate School of Universitas Syiah Kuala, 2023)
It is crucial to perform routine bridge maintenance in order to evaluate the structure's current state. As a result, it is possible to guarantee that the bridge structure can offer services that are both comfortable and secure. The bridge structure being able to reach the service life as planned is another goal that can be accomplished. Visual inspection or the use of some currently popular sensors can be used to monitor the condition of the bridge. The dynamic properties of a structure including modal frequency and mode shape will be used to determine the structure's present and potential future conditions. Using a velocitymeter, vibration data collection is conducted as the first step. The next step is analyzing data to determine natural frequency. The fundamental frequency of the Tugu Suharto bridge structure in Semarang was determined to be 3.995 Hz. Future bridge structure condition monitoring can be done using frequency data and finite element model. The condition of bridge infrastructure in the future for one city is an important thing that must be considered. Some bridges are classified as structurally deficient, and many bridges are nearing the end of their design lives. The next generation of Semarang highway bridges is currently being designed and built, but existing bridges still need to be maintained through proper inspection and load rating. In order to incorporate structural modeling, instrumentation, and nondestructive testing into the design, construction, and management of bridges, this study proposes an objective load rating protocol. Using information gathered from structural health monitoring (SHM), a baseline structural model is developed and verified. The load rating factors of the bridge are then determined using the structural model under both real-condition and simulated damaged conditions.